Vitamin A dan Obat Cacing untuk Anak di RT 49 Sepinggan pada Masa Pandemi Covid-19 - Rahayu Sri Waskitoningtyas; Ryan Angga Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
The purpose of this PkM is to find out how the service of providing vitamin A and deworming medicine during the Covid-19 pandemic to children in Sepinggan Village and how parents responded to the administration of Vitamin A and Deworming medicine during this pandemic The research subjects here are children who are in Melati Housing Phase 5, Sepinggan Village. Data collection methods are interviews and documentation. Interviews were conducted with parents and children. While the documentation is in the form of the name of the child who was given vitamin A and worm medicine. The data analysis technique uses source triangulation. Based on the results, it was found that vitamin A was given to toddlers, blue was given to children under 1 year of age, while red vitamin A was given to toddlers aged 1 to 5 years. Children aged 1 year to 2 years are given deworming medicine, which is half a tablet, while for children from two years to 12 years, one tablet of deworming is given. The parents' response was very good for this gift, because parents don't need to come to the puskesmas to ask for Vitamin A and Deworming Medicine, there is already a representative from the Posyandu to give Vitamin A tablets and Deworming Medicine, besides that during this pandemic, parents are also very worried to crowd and congregate in too many numbers.